Macroalgas bentónicas de la laguna de Tampamachoco, Veracruz, México - Dreckmann, Kurt M (Universidad de Costa Rica, 1994)
A total of 23 macroalgal species were identified in Laguna Tampamachoco, Veracruz, Mexico: 9 ChIorophyceae, 2 Phaeophyceae and 12 Rhodophyceae. Algal richness per area is relatively higher (60-100 times) than in another coastal lagoon and one estuary of the area (Laguna Madre and Tamiahua with 29 and 22 species respectively). We report the presence of Phaeophyceae in this environment for the first time. The three sites have 58 species in total, twice the number reported from any other North Atlantic estuarine region.